2011
DOI: 10.1039/c0cc05313a
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of the electrode potential on the metal–adsorbate surface states: relevant states in the charge transfer mechanism of SERS

Abstract: Quantum mechanical calculations of the ground and excited electronic states of several [Ag(n)-pyridine](q) complexes yield a linear dependence of the energies of the surface states, especially the metal-to-molecule charge transfer states, on q(eff) = q/n. This is the first theoretical approach to modelling the effect of the electrode potential on SERS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 18 publications
2
49
0
Order By: Relevance
“…Second, the line shape of the intensied modes is not so sharp as in other SERS spectra containing pyridine derivatives. [14][15][16][17] Third, the relative intensities of the bands depend moderately on the electrode potential; this is especially notable for the 8a mode of pyridyl moiety ($1600 cm À1 ), which is found strongly sensitive to the electrode potential for other compounds as pyridine and its derivatives whose enhancement is related to the SERS-CT mechanism given that the energy of the CT transition should be very dependent on the applied potential. 15 In what follows, the analysis of the spectra will be based on the premise that metal and adsorbate form the metal-adsorbate (M-A) surface complex which is considered as a single chemical species.…”
Section: Sers Spectra On Silver Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…Second, the line shape of the intensied modes is not so sharp as in other SERS spectra containing pyridine derivatives. [14][15][16][17] Third, the relative intensities of the bands depend moderately on the electrode potential; this is especially notable for the 8a mode of pyridyl moiety ($1600 cm À1 ), which is found strongly sensitive to the electrode potential for other compounds as pyridine and its derivatives whose enhancement is related to the SERS-CT mechanism given that the energy of the CT transition should be very dependent on the applied potential. 15 In what follows, the analysis of the spectra will be based on the premise that metal and adsorbate form the metal-adsorbate (M-A) surface complex which is considered as a single chemical species.…”
Section: Sers Spectra On Silver Electrodementioning
confidence: 99%
“…[14][15][16][17] Third, the relative intensities of the bands depend moderately on the electrode potential; this is especially notable for the 8a mode of pyridyl moiety ($1600 cm À1 ), which is found strongly sensitive to the electrode potential for other compounds as pyridine and its derivatives whose enhancement is related to the SERS-CT mechanism given that the energy of the CT transition should be very dependent on the applied potential. 15 In what follows, the analysis of the spectra will be based on the premise that metal and adsorbate form the metal-adsorbate (M-A) surface complex which is considered as a single chemical species. Although the composition and structure of such a complex is unknown, we have shown in previous works [8][9][10][11][12][13][14][15][16][17][18][19] that this species and the effect of the electrode potential on it can be modeled by an adequate choice of the adsorbate bonded through the nitrogen atom of the pyridyl group to linear metallic Ag n q clusters with different densities of charge.…”
Section: Sers Spectra On Silver Electrodementioning
confidence: 99%
“…6 The enhancement field surrounding the metal nanoparticle may extend several nanometres from the nanoparticle surface. [7][8][9][10] In the particular case of the detection of explosives in solution, a range of noble metal-based SERS substrates have been used, including thin films of noble metal nanostructures and composites of noble metals with transition metals or semiconductors. [11][12][13] Recently, Jamil et al detected femtomolar levels (100 fM) of trinitrotoluene (TNT) with high reproducibility using a substrate consisting of gold nanostructures deposited on a flat gold disc.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the adsorption of aromatic molecules on silver is often accompanied by the metal‐adsorbate charge transfer that is strongly affected by the surface potential . The above results for neocuproine suggest that the freer rotation of the methyl groups at more negative electrode potential takes place due to the charge transfer process.…”
Section: Resultsmentioning
confidence: 91%